2021
DOI: 10.1109/access.2021.3051049
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Reliability of the Prediction of Terrestrial Water Storage in Yunnan Using the Artificial Neural Network Selective Joint Prediction Model

Abstract: Although Gravity Recovery and Climate Experiment (GRACE) can provide accurate estimates in water storage, there are about 11 months gaps between GRACE and its successor GRACE-Follow On (GRACE-FO). To improve the accuracy of bridging the gaps, this study combines the partial least squares regression (PLSR) model with the learning-based models for the first time, and construct an artificial neural network selective joint prediction model. To this end, the performance of combination of PLSR and nonlinear autoregr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…There were temporal gaps between GRACE and GRACE-FO with a length of approximately 14 months. Many studies have reported on the gap filling between GRACE and GRACE-FO temporal data using interpolation (linear [48], singular spectrum analysis [48], and cubic spline [49], [50]). Reference [48] applied linear interpolation to fill the gap and confirmed that the trend is positively biased by over 10% compared to the original series.…”
Section: ) Grace and Grace-fo Satellite Mascon Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were temporal gaps between GRACE and GRACE-FO with a length of approximately 14 months. Many studies have reported on the gap filling between GRACE and GRACE-FO temporal data using interpolation (linear [48], singular spectrum analysis [48], and cubic spline [49], [50]). Reference [48] applied linear interpolation to fill the gap and confirmed that the trend is positively biased by over 10% compared to the original series.…”
Section: ) Grace and Grace-fo Satellite Mascon Solutionmentioning
confidence: 99%
“…Nevertheless, since no data can replace the GRACE and GRACE-FO data, the interpolation method is widely used. In this study, a cubic spline suitable for time series interpolation was applied [49], [50].…”
Section: ) Grace and Grace-fo Satellite Mascon Solutionmentioning
confidence: 99%
“…The impact of the FN method's selection on the algorithm's performance has been experimentally studied by some researchers [30]- [33] to estimate the most appropriate one for a given problem. But, it remains the extended approach of employing the min-max normalisation method before the use of an ANN [34]- [38].…”
Section: Introductionmentioning
confidence: 99%